Recollect: home video and the autobiographical self - Comninos, Nicola (My University, 2015)
This research looks at home video footage and family photographs as part of the visual portrait of a curated record of the autobiographical self. The research includes a written thesis exploring the theoretical concerns and provides a reflexive analysis of the creative component of the PhD, which is a 60-minute documentary film. The research, both creative and written, assesses how autobiographical memory is informed and shaped by home video recordings, and how new digital formats have allowed home video to collapse the boundaries between the personal and the public. It also explores how personal narratives speak to the wider socio-political and cultural concerns of a particular time. These ‘collapses’ between boundaries provide a playful, pluralistic approach to a history of the self. The many paradigms that coexist within the work – the past and the present, time and space, previously accepted narratives and newly formed ones – do not exist as binary to each other, but rather exist in conversation with each other and serves to explore the ever elastic subject/object dichotomy. The autobiographical film is titled Fraternal, with the tagline ‘The future isn’t like it used to be’. It tells the emotional story of the relationships between myself and my twin, and our parents – the hellos and goodbyes, arrivals and departures, beginnings and endings that happen within family ties. The film is set against the backdrop of the political situation in southern Africa during the 1980s and 1990s. It is cut predominantly from personal home video footage: a mixture of Super 8mm, Hi8 and DV footage shot largely between 1984 and 1994 in Zimbabwe and South Africa
A thesis submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2015
Keywords: Autobiography; Autobiographical memory in motion pictures; Self-presentation; Photography--Social aspects; Stock footage; Video recordings--Social aspects; Photography of families; Time in motion pictures